2022
DOI: 10.1002/joc.7541
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated exacerbation of global extreme heatwaves under warming scenarios

Abstract: It is generally believed that global warming drives an increase in heatwaves, but these changes vary regionally. Projected trends of heatwaves and comparisons between observed and projected heatwave trends are poorly understood. We selected multiple characteristics of global heatwave events, including indicators on heat-related health impacts under historical and future scenarios from the NASA Earth Exchange/Global Daily Downscaled Projections (NEX-GDDP) dataset. We quantified the trends in the frequency, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Seminal work from Lind ( 1963 ) indicated that after body core temperature inflection, humans could remain in the heat for up to 8 h before falling out of the “prescriptive zone” while performing work. Future work should examine rates of heat storage after inflection is achieved to further our understanding of how long humans could safely stay in the heat if forced to, especially in a world of increased, sustained heat (Han et al 2022 ) and the risk of infrastructure failure, which inhibits cooling mechanisms such as fans and air conditioning (Perera et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seminal work from Lind ( 1963 ) indicated that after body core temperature inflection, humans could remain in the heat for up to 8 h before falling out of the “prescriptive zone” while performing work. Future work should examine rates of heat storage after inflection is achieved to further our understanding of how long humans could safely stay in the heat if forced to, especially in a world of increased, sustained heat (Han et al 2022 ) and the risk of infrastructure failure, which inhibits cooling mechanisms such as fans and air conditioning (Perera et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is virtually certain that heatwaves have become more frequent and more intense across most land regions since the 1950s (Allan et al., 2021; Han et al., 2022). For instance, Perkins‐Kirkpatrick and Lewis (2020) found that the world has experienced an average increase of 2.26 more heatwave days per decade since 1950, with substantial inter‐regional variations in the overall extreme heat being experienced.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, extreme climatic events, characterized as abrupt meteorological phenomena exhibiting intensity and/or impacts that deviate significantly from historical variability, are becoming frequent and intense (Allan et al., 2021). There is growing evidence that simultaneous or successive heatwaves and droughts, wild fires and floods have increased in recent decades (Coumou & Rahmstorf, 2012; Han et al., 2022; Ma et al., 2020; Raymond et al., 2020; Zscheischler et al., 2020), which have the potential to exacerbate the loss of species and ecosystem degradation driven by anthropogenic pressures (Allan et al., 2021; Fey et al., 2015; Rahmstorf & Coumou, 2011; Ummenhofer & Meehl, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lesueur’s Velvet Gecko ( Amalosia lesueurii ) inhabits sandstone and granite rock outcrops in eastern Australia and occurs from southeastern New South Wales to southeastern Queensland [ 29 ]. In southern populations, adults mature at age 2 to 3 years, and live for up to 13 years in the wild [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Velvet geckos are vulnerable to high temperatures because females lay eggs in communal nests in rock crevices, and nest temperatures are positively correlated with air temperatures [ 28 ]. Thus, if the intensity and duration of summer heatwaves increases in the future, as predicted by climate modelers [ 22 , 29 ], then nest temperatures may shift upwards. Although velvet geckos are not reported to have TSD, they are nonetheless at risk from warming because incubation-induced changes in hatchling survival rates can increase the risk of local extinctions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%